Role of the mental representation in enhancing motor learning and performing gymnastic element - Wali-Menzli, S.; Hammoudi-Nassib, S.; Ismail, S.; Hammoudi, S. R.; Knani Hamrouni, I.; Jarraya, M. (Science of Gymnastics Journal, 2019)
The aim of the present study was to analyze the effect of three intervention modalities ((a) external visual imagery modality, (b) verbal feedback modality and (c) visualization modality) on the Roll backward to handstand. 42 females` students (age 20.6 ± 1.3 years) voluntarily took part in this study. Subjects were assigned into three groups according to three learning modalities: mental imagery modality, verbal feedback modality and visualization modality. During the two testing sessions (before and after training sessions), the participant was marked according to the FIG Code of Points. The results thus reveal a significant effect on the training, therefore on the learning of the backward roll followed by a handstand by the method of mental imagery. Thus, the mental imagery seems to be a tool for transmission of knowing and training by excellence making it possible to the students to progress while getting rid of the lack of motivation, organization, implication and work. Moreover, the results gathered following the gymnastic practice also show an improvement of the performance of the first group that had to undergo training by verbal feedback. This supports the idea that the training by the method of verbal feedback improves the technical performance of a gymnastic element. However, the method of training by visualization of a model appears to be the less developed by the participants in comparison with the mental imagery and the verbal Feedback.